Plume Activity on Europa: Current Knowledge and Search Strategy for Europa Clipper - Lorenz Roth; Erin Leonard; Kelly Miller; Matt Hedman; Lynnae C. Quick; Tracy M. Becker; Shawn Brooks; Corey Cochrane; Ashley Gerard Davies; Carolyn M. Ernst; Cyril Grima; Candice J. Hansen; et al. (The Planetary Science Journal)
The presence of cryovolcanic activity in the form of geyser-like plumes at Jupiter’s moon Europa is a much-debated topic. As an active plume could allow direct sampling by a passing spacecraft of a potentially habitable interior environment, the detection and analysis of ongoing plume activity would be of the highest scientific value. In the past decade, several studies have interpreted different remote and in situ observations as providing evidence for large gaseous plumes at different locations on Europa. However, definitive proof is elusive, and visible imaging data taken during spacecraft flybys do not reveal clear indications of ongoing activity. After arrival at Jupiter in 2030, the NASA Europa Clipper spacecraft will systematically search for and constrain plume activity at Europa utilizing a variety of investigations and methods during, before, and after close flybys. Given the lack of a confirmed plume detection to date, the Europa Clipper science team has adopted a global plume search strategy, not focusing on any specific geographical area or any specific type of observation. This global search strategy assigns enhanced value to data obtained early in the mission, which allows time for further observations and characterization of any observed plume at later times. Here we describe the current state of knowledge on plume activity, the Europa Clipper search strategy, and the role of various instruments on the Europa Clipper payload in this search.